2019
DOI: 10.3390/f10060467
|View full text |Cite
|
Sign up to set email alerts
|

Wild Edible Fruits: A Systematic Review of an Under-Researched Multifunctional NTFP (Non-Timber Forest Product)

Abstract: Wild edible fruits (WEFs) are among the most widely used non-timber forest products (NTFPs), and important sources of nutrition, medicine, and income for their users. In addition to their use as food, WEF species may also yield fiber, fuel, and a range of processed products. Besides forests, WEF species also thrive in diverse environments, such as agroforestry and urban landscapes, deserts, fallows, natural lands, and plantations. Given the multifunctional, ubiquitous nature of WEFs, we conducted a systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 203 publications
(325 reference statements)
0
60
1
1
Order By: Relevance
“…Increasing evidence suggests that the quality and quantity of chemical metabolites in plants are influenced by a multitude of factors especially the environmental conditions (Ncube, Finnie, & Van Staden, 2012). b. Indiscriminate and illegal logging: Indiscriminate cutting of trees is a common act in the rural communities in Africa, and this has immeasurably contributed to the depletion of the population of indigenous fruit trees (Sardeshpande & Shackleton, 2019). This unregulated tree felling may be attributed to poverty, food insecurity, and high rate of unemployment among the young populations (Baldermann et al, 2016).…”
Section: With Unlocking the Potential Of The 10 Selected Indigenous Fmentioning
confidence: 99%
“…Increasing evidence suggests that the quality and quantity of chemical metabolites in plants are influenced by a multitude of factors especially the environmental conditions (Ncube, Finnie, & Van Staden, 2012). b. Indiscriminate and illegal logging: Indiscriminate cutting of trees is a common act in the rural communities in Africa, and this has immeasurably contributed to the depletion of the population of indigenous fruit trees (Sardeshpande & Shackleton, 2019). This unregulated tree felling may be attributed to poverty, food insecurity, and high rate of unemployment among the young populations (Baldermann et al, 2016).…”
Section: With Unlocking the Potential Of The 10 Selected Indigenous Fmentioning
confidence: 99%
“…The study area, the Indian Ocean Coastal Belt (IOCB), is host to rich biodiversity [56] and dense human population, is undergoing rapid land cover change [57], and urban foraging is highly prevalent in this region (Sardeshpande and Shackleton unpublished data). We focus on the planting and foraging of wild edible fruit species, because they are (i) widely foraged globally [58], within South Africa [59], and in the study area (Sardeshpande and Shackleton unpublished data), (ii) commonly found in the wild as well as in human-dominated landscapes including agroforestry systems, home gardens, and urban green spaces [60], (iii) significant contributors to nutrition and income across the socioeconomic and rural-urban gradient [23], (iv) often resilient to climatic and harvesting pressures [61], and (v) potentially important to urban biodiversity, particularly frugivores and pollinators [62]. South Africa is among the most unequal economies in the world ( [63], p. 21), with a quarter of its population living below the food poverty line ( [63], p. 14).…”
Section: Study Areamentioning
confidence: 99%
“…debarking, lopping). This is empirically true [61,106], but different species respond differently to varying degrees of harvest [62], and therefore all stakeholders should be equipped with knowledge on best practices including lowimpact harvest and the quantities that may be safely harvested for each species. In some cases, locals who have used the species over generations may already possess appropriate traditional knowledge about sustainable harvest [107].…”
Section: Plos Onementioning
confidence: 99%
“…Thus, WETs are an important source of sustenance for many people in developing countries [6,14], improving household food security under normal circumstances as well as during crop scarcity periods [15][16][17] in urban and rural contexts [18]. Furthermore, WETs can represent important sources of income for their users [19,20].…”
Section: Introductionmentioning
confidence: 99%